Development and Validation of New Rp-Hplc Method for The Simultaneous Estimation of Lamivudine, Tenofovir and Doravirine in Pharmaceutical Dosage Form - Srinivas, MNB.; devi, Dharmasoth Rama; Ramesh, Ch.; Krishna, Radha; Basavaiah, K. (International Journal of Membrane Science and Technology, 2023)
A simple, accurate, and precise quantitative approach for the simultaneous quantification of Lamivudine, Tenofovir, and Doravarine in pharmaceutical dose form was developed. The chromatogram was performed on an Inertsil C18, 150 * 4.6mm, 5µm column with a mobile phase containing 0.1% orthophosphoric acid and Acetonitrile in a 50:50 v/v ratio that was pumped through the column at a flow rate of 1ml/min. The temperature was kept at 30°C. The optimal wavelength was 230.0 nm. Lamivudine, Tenofovir, and Doravarine had retention times of 2.238, 2.623, and 3.088 minutes, respectively. For three medications evaluated, the % RSD of system precision and method precision was determined to be less than 2%. The mean % recovery for Lamivudine, Tenofovir, and Doravarine was 101.32 percent, 99.94 %, and 100.61 %, respectively. The method was found to be simple, accurate, sensitive,cost effective and can be useful in routine quality control analysis.